Exemplarily view on selected fluorescence textile products - Boris Mahltig; Vanessa Ernst; Lisa Schöder (Communications in Development and Assembling of Textile Products)
Fluorescent materials emit light of higher wavelength, in case of illumination with light exhibiting lower wavelength. In many commercial applications, fluorescent materials transfer non-visible ultraviolet (UV) light into visible light. By this an additional color effect and higher visibility is reached. One typical field for application of fluorescence dyes is the textile area. Here, fluorescent textile products are manifold used and offered, e.g. for brightening effects, light effects and UV protection. With this background, the aim of the current study is the investigation of typical commercially available textile products with fluorescent properties. For this, four different polyester fiber-based materials of different coloration and purpose are selected for investigation. Investigations are performed by illumination under different illumination arrangements with UV light and visible light. CIE-Lab measurements are done. Further, scanning electronic microscopy (SEM) and Fourier Transform infrared (FT-IR) spectroscopy are used. Light emission and excitation of the samples is recorded by fluorescence spectroscopy. 2D fluorescence spectroscopy is performed. The chemical composition of the investigated textile samples is determined by using electron dispersive spectroscopy (EDS). For all investigated commercial textile products, the light emission during illumination with UV light is extraordinary strong. The color appearance can be enhanced strongly by this fluorescence effect. Beside the absorption of UV light by the present fluorescence dyes, also the presence of titanium dioxide supports an UV protective property of the textile samples. Finally, it can be concluded that fluorescent fiber materials are well established products for advanced and functional textiles. These materials can be even found in cost effective and everyday consumer products.